FORECASTING HIV PREVALENCE AMONG INDIVIDUALS AGED 15-49 YEARS IN GUYANA USING HOLT’S LINEAR METHOD - Dr. Smartson. P. NYONI; Thabani NYONI (Web of Journals Publishing, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Guyana from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s linear exponential smoothing model. The optimal values of smoothing constants α and β are 0.9 and 0.5 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will decline over the out of sample period. Therefore, there is need to strengthen HIV case detection and HIV prevention among key populations and vulnerable groups.
Keywords: Exponential smoothing, Forecasting, HIV prevalence.